Halal tourism in Southeast Asia: past, present and future trends - Rahman, Md Roshidur; Mohamad Reeduan, Mustapha; Muhammad Ashraf, Fauzi (Emerald Publishing, 2026)
Purpose: Halal tourism has grown substantially in Southeast Asia, driven by rising Muslim populations, economic growth and increased demand for Shariah-compliant travel services. This study aims to systematically review the development of halal tourism research in the region by identifying influential contributions, thematic trends and future research directions. Design/methodology/approach : This study used a bibliometric analysis using 204 peer-reviewed journal articles retrieved exclusively from the Scopus database. The selection criteria included English-language publications focused on halal tourism in Southeast Asia, published between 2011 and 2024. To examine the intellectual structure and thematic development of the field, three bibliometric techniques were applied using VOSviewer software: citation analysis to identify influential works, co-citation analysis to uncover conceptual relationships and co-word analysis to detect emerging research themes. Findings: This study reveals four major research clusters in the co-citation and six clusters in the co-word analysis. Theoretical and practical implications are presented in developing the potential of halal tourism in Southeast Asia. These clusters reflect the field’s progression from conceptual foundations to consumer behavior and policy concerns. Although halal tourism has gained momentum, gaps remain in empirical depth, standardization and regional coordination. Originality/value: This study offers a comprehensive overview of the scholarly evolution of halal tourism in Southeast Asia by applying bibliometric techniques to Scopus-indexed literature. Key publications within each cluster are referenced to strengthen the analysis. This study also provides concrete recommendations for future development, including the need for The Association of Southeast Asian Nations-wide halal tourism standardization to improve consistency and cross-border collaboration. These contributions offer researchers, practitioners and policymakers a clearer understanding of the field’s development and future directions.